Análisis de redes sociales de productividad científica de los participantes en el “XI Encuentro Nacional y IV Internacional de investigadores de las Ciencias Pecuarias – ENICIP (2011)
ABSTRACT: The XI National and IV International meeting of animal and veterinary sciences (ENICIP) has been gathering researchers to socialize their advances to the scientific community since 1989. It is perceived in this meeting the presence of wide relations among researchers and institutions in the different areas of animal and veterinary science. Objective: to identify the social networking of scientific productivity in the areas of the animal and veterinary sciences. Methods: data from the authors that submitted research papers to ENICIP 2011 was collected. A matrix array for papers by author, papers by topic and authors by topic was used. The arrays were analyzed with UCINET® software. Results: 1270 researchers submitted 560 abstracts in 20 different areas. The areas with highest participation of researchers were animal nutrition and feeding (252), epidemiology and public health (153) and pastures and silvopastoral systems (131). The areas with the highest number of submitted abstracts were animal nutrition and feeding (103), animal breeding and genetics (53) and pastures and silvopastoral systems (48). Solid clusters between researchers, and new researchers with high productivity, but low social relations were found. Conclusion: the scientific communities in agricultural sciences shows high interrelationship among its different areas; nevertheless higher interrelationship among researchers from different institutions would be advantageous.